Convective heat transfer prediction in disk-type electrical machines. (5th December 2015) - Rasekh, Alireza; Sergeant, Peter; Vierendeels, Jan
Abstract: This paper presents correlations to assess the average convective heat transfer in axial flux permanent magnet machines based on numerical simulations. The rotor–stator system is enclosed in a cylindrical chamber, and all the surfaces within the machine are considered isothermal, each on their own temperature. CFD simulations have been performed for different ranges of the rotational Reynolds number, Re = ωR 2 / υ, the gap size ratio, G = s / R and the surface temperature of the rotor, the stator and the cover. The average convective heat transfer coefficients for all surfaces are defined. The bulk flow temperature has been taken into account as the reference temperature instead of the ambient temperature to calculate the average heat transfer coefficient. The latter is typically used in literature to describe the heat transfer between the rotor and the stator, but the heat transfer coefficient is then only applicable for a given surface temperature of the rotor and the stator, which is a serious drawback. Therefore, in order to calculate the bulk fluid temperature, we average the values of fluid temperature adjacent to the corresponding surface; by doing so, the average convective heat transfer in the gap becomes independent of the ambient temperature. Thereafter, for estimating the bulk fluid temperature, a linear correlation between the surface temperature of the rotor, the stator and the cover is made. The unknown coefficients of that linear equation are found with the aid of the least squares method. Afterward, the appropriate equations for the mean Nusselt number are given through curve fittings. The proposed empirical correlations are applicable to various geometries and boundary conditions. Results are compared with the available data in literature and good agreement has been found. It is shown that, for a given Reynolds number, there is a gap size ratio for which the average convective heat transfer of the stator surface in the gap reaches a minimum. Moreover, it can be concluded that the proposed correlation is a quite versatile tool for thermal modeling of disk type electrical machines. Highlights: We discuss the convective heat transfer modeling in disk type electrical machines. Bulk fluid temperatures adjacent to each surface are predicted by a linear formula. The use of bulk fluid temperature makes the correlation more generally applicable. The proposed correlations are independent of the ambient temperature. Convective heat transfer for stator reaches a minimum at a certain gap size ratio.